The Image Of Generational Memory And Human Responsibility For The Future In The Works Of Chingiz Aitmatov - Alimkulov Abdurasul Ergash O'g'li; Turg'unov Ulug'bek Bahodir o'g'li (Zien Journals, 2025)
The article examines the central problem of historical memory and moral responsibility to future generations in Chingiz Aitmatov's works. The key works of the writer ("The Day Lasts More Than a Hundred Years", "The Scaffold", "Burannyi Polustanok") are analyzed, in which the concept of memory is revealed through mythological images, national traditions, and philosophical understanding of the connection between times. Special attention is paid to Aitmatov's interpretation of the phenomenon of mankurtism as the loss of historical memory and national identity. The methodological basis of the study is the cultural-historical and philosophical-anthropological approach to the analysis of literary text
Keywords: Ch. Aitmatov; historical memory; mankurtism; responsibility of generations